Influence of mode confinement factor on the modulation properties of the Vertical Cavity Surface Emitting VCSEL laser - Afrah Kareem; Younis Qurot (College of Education for Pure Sciences, 2021)
Vertical cavity surface emitting laser VCSEL is currently the main solution for many technological aspects, ultrafast optical interconnecting, Gigabit Ethernet, etc. In this paper we present the simulation results by using Optiwave™ software version 7, of the effects of optical mode confinement factor on the modulation properties)which inspected by eye diagram of the received signals)of the vertical cavity surface emitting laser VCSEL, with the range (8-20)Gbps of pseudo random bit sequence PRBS. The quality of the VCSEL modulation have been inspected by time domain signals, spectrums and eye diagram. Simulation results appeared an improvement in the characteristics of received bit sequences of (8, 10, 12.5, 16 and 20)Gbps bit rates, represented by the rising the value of quality factor QF (1.77 to 4.81) versus increasing the value of optical mode confinement factor Γ(0.2 to 0.5) respectively, and a decreasing in jitter time of superimposed traces of eye pattern and well opining eye pattern. And in the corresponding, the bit error rates BERs of the received signals have been decreased, with rising the value of mode confinement factor Γ of the laser at constant modulation index and constant temperature of the laser. Also, the VCSEL's modulation response differences with different bitrates, causes different values of QF and BER for individual value of mode confinement factor Γ.